Cor luz - cor pigmento: a física e as artes - Curcio, Ítalo Francisco (2013)
Science and Art are two concepts that have been greatly evolved throughout history, mainly due to cultural evolution experienced by humanity itself. Science, in its primitive stage, as synonymous of knowledge, preceded the Arts. However, according to its current concept considered as a result of the proposed method, by Francis Bacon, it is a recent phenomenon when compared to the period of human existence on Earth. Thus, Art preceded Science, because from its beginning it always configured as such, despite the different ways in which it has been presented. This is why the term Arts is used instead of Art. Among the Sciences, separated as Natural Sciences and Humanities, Physics stands out, even in the primitive stage of science, always referred to Nature as a whole, justifying its etymology Physics, the Greek Physis that means Nature and, according to available records, developed with the Arts since prehistory. In this context, this work, which presents a brief history of the evolution of perception and color reproduction by man, has as main attribute a study of the concept of color, pigment and light as taking Physics as a foundation, according to the branch of knowledge called Optics. From a literature search, the author s and other expert s experiences, both in Arts and in Science in General, an approach of Arts and Physics is presented, in terms of interdisciplinarity that exists between the color theme and concepts of physical optics, as one of the branches of this science. Records used are based on works that still exist, such as cave paintings and paintings in other processes, frescoes and sculptures, as well as the bibliography, documents preserved in museums, libraries and cultural venues, and statements from researchers, due to their own works. It was also included in this compilation the development of some technics of color reproduction, both in pictorial art, using pigments, as in architectural lightening projects, fabrication of transparent and colored glasses and at photographic, cinematographic and digital arts from light sources, in its different ways of generation and applications.